KONSTRUKSI MAKNA BIGO LIVE BAGI PENGGUNA DI KALANGAN UNIVERSITAS RIAU - Yoasta, Mentari Endrilla; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Bigo live is one of the social media that become viral among students in the University of Riau today which became a unique phenomenon of its own. Bigo Live is exist because of the uniqueness features it has, as if feature live streaming, video call and give. Departing from the motive, meaning, experience of the students users of Bigo Live which is very viral at this time. This study aims to determine the motives of students using Bigo Live among the University of Riau, meaning of Bigo Live features For students in the University of Riau, and the experience of Bigo Live users among the University of Riau. This research method is using a qualitative research method with phenomenological approach. The informants in this study were five users of Bigo Live who selected using purposive technique. Data was collected through in-depth interviews, participant observation, and documentation. This research uses an interactive data analysis model of Miles and Hubermen, using the technique of examining the validity of data through the extension of participation and triangulation. The results of this study indicate that the motives of Bigo Live users is the motive of the past (because motive) in the form of friend invitation, kepo (knowing every particular object) and trend, and the future motive (in order to motives) in the form of interaction with new people and expertise. The meanings of Bigo Live features for students include Bigo Live as a medium of entertainment, Bigo Live as a Media lecture and Bigo live as an expression of feelings. The communication experience of Bigo Live user is a pleasant experience (Positive) includes adding friendship network, build a good relationship with users and entertaining yourself. Unflattering (negative) experiences include blasphemous accounts resulting in discomfort, and Bigo Live users who use Bigo Live badly.